PENGUATAN PERAN LEMBAGA KELOMPOK TANI DALAM PENGEMBANGAN USAHA TANI KOPI RAKYAT (Studi Kasus Kelompok Tani di Desa Sidomulyo Kecamatan Silo Kabupaten Jember) - Hesti Herminingsih (University of Jember, 2011)
The objectives of this study were as follows to analyze the role of farmer group in development of coffee farming. The study was designed as a descriptive correlation study that conducted in January-March 2010.The number of 64 respondents using proportionate stratified random sampling method of all smallholder coffee farming groups in Sidomulyo Village Silo District Jember Regency. Primary and secondary data were analyzed using descriptive and inferential statistics with Rank Spearman correlation. Results showed that there were production unit, economic unit and learning proces has significantly correlation with facility of farming, economic unit and learning proces has significantly correlation with harvest process variable; and economic unit has significantly correlation with postharvest coffee farming.Key Words: robusta coffe, farmer group, intitutions